2020
DOI: 10.1128/mbio.01060-20
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling between the Unfolded Protein Response and Endoplasmic Reticulum/Golgi Ca 2+ -ATPases Promotes Stress Tolerance, Cell Wall Biosynthesis, and Virulence of Aspergillus fumigatus

Abstract: Many species of pathogenic fungi deploy the unfolded protein response (UPR) to expand the folding capacity of the endoplasmic reticulum (ER) in proportion to the demand for virulence-related proteins that traffic through the secretory pathway. Although Ca2+ plays a pivotal role in ER function, the mechanism by which transcriptional upregulation of the protein folding machinery is coordinated with Ca2+ homeostasis is incompletely understood. In this study, we investigated the link between the UPR and genes enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 65 publications
4
23
1
Order By: Relevance
“…Dithiothreitol (DTT) is the most widely used approach to experimentally induce ER stress because it reduces the disulfide bridges that stabilize many proteins in the secretory pathway, resulting in a rapid increase in the level of unfolded proteins that activate the IRE1/IreA sensor ( 32 ). Consistent with previous reports ( 33 ), DTT treatment of A. fumigatus hyphae induced accumulation of hacA i mRNA, reflecting activation of the IreA RNase domain ( Fig. 2A ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Dithiothreitol (DTT) is the most widely used approach to experimentally induce ER stress because it reduces the disulfide bridges that stabilize many proteins in the secretory pathway, resulting in a rapid increase in the level of unfolded proteins that activate the IRE1/IreA sensor ( 32 ). Consistent with previous reports ( 33 ), DTT treatment of A. fumigatus hyphae induced accumulation of hacA i mRNA, reflecting activation of the IreA RNase domain ( Fig. 2A ).…”
Section: Resultssupporting
confidence: 93%
“…The compound also blocked the ability of DTT to induce the expression of srcA and pmrA ( Fig. S2A ), encoding ER/Golgi P-type Ca 2+ ATPases that we have recently identified as targets of the UPR in A. fumigatus ( 33 ). Interestingly, we found that a Δ srcA /Δ pmrA double deletion mutant was hypersensitive to the effects of 4μ8C relative to its parental strain ( Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Pathogenic fungal lifestyle is largely supported by the ER, which enables secretion of cell wall components and virulence-related proteins. 41,42 Our results show that the cell wall structure and components were drastically affected in the absence of Macwh1 or Macwh43. Thus, the roles of MaCwh1 and MaCwh43 in fungal tolerance to CFW were less likely to be associated with the domains in CWH43 than with the secretion and remodeling of cell wall components by ER.…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with an ER localization of Cwh43 in S. cerevisiae and S. pombe , 24,40 both MaCwh1 and MaCwh43 were localized at the ER. Pathogenic fungal lifestyle is largely supported by the ER, which enables secretion of cell wall components and virulence‐related proteins 41,42 . Our results show that the cell wall structure and components were drastically affected in the absence of Macwh1 or Macwh43 .…”
Section: Discussionmentioning
confidence: 79%